Decolonizing understanding: language and translation in the social sciences - Baumann, Benjamin; Rehbein, Boike (Global handbook of inequality, 2024)
The chapter argues that in social science research, especially when it takes place in sociocultural configurations that differ from that of the researchers, it is not just language and cultural barriers that need to be overcome. In addition, researchers must also take into account that the study subject itself, i.e., society or an aspect of it, is imagined and experienced completely differently. In order to clarify this, the chapter first considers the relationship between language and society and then takes a closer look at understanding in the social sciences. The discussion of the concept of understanding shows that from a social science perspective, it is not only important to understand meanings, symbols and practices, but also an ‘existence’ (Dasein) in the Heideggerian sense. Human existence is essentially social and strongly determined by social structures. Conversely, social structures are at least partially meaningful and must be embodied in order to exist. Knowing how to behave properly and meaningfully in a given social context is a tacit form of knowledge that rests on the incorporated interpretation of collectivity that is shared by members of a language game. We refer to this incorporated interpretation of collectivity as social ontology. The article explores what a social ontology is and what social scientific translation between social ontologies means. These structuring questions are explained using the example of a case study from rural Thailand.